SCAI Expert Consensus Statement on the Management of Calcified Coronary Lesions - Riley, Robert F.; Patel, Mitul P.; Abbott, J. Dawn; Bangalore, Sripal; Brilakis, Emanouil S.; Croce, Kevin J.; Doshi, Darshan; Kaul, Prashant; Kearney, Kathleen E.; Kerrigan, Jimmy L.; McEntegart, Margaret; Maehara, Akiko; et al. (Journal of the Society for Cardiovascular Angiography & Interventions, 2024)
The prevalence of calcification in obstructive coronary artery disease is on the rise. Percutaneous coronary intervention of these calcified lesions is associated with increased short-term and long-term risks. To optimize percutaneous coronary intervention results, there is an expanding array of treatment modalities geared toward calcium modification prior to stent implantation. The Society for Cardiovascular Angiography and Interventions, herein, puts forth an expert consensus document regarding methods to identify types of calcified coronary lesions, a central algorithm to help guide use of the various calcium modification strategies, tips for when using each treatment modality, and a look at future studies and trials for treating this challenging lesion subset.